The search for Winchester's Anglo-Saxon minsters - Biddle, Martin 1937- (Winchester Excavations Committee, 2018)
This title provides a history of extensive archaeological excavations in Winchester from 1961 to 1970, showing how they led to the discovery of the Old and New Minsters and brought back to life the history, archaeology, and architecture of the city's greatest Anglo-Saxon buildings